Cutting edge: CD4+CD25+ alloantigen-specific immunoregulatory cells that can prevent CD8+ T cell-mediated graft rejection: implications for anti-CD154 immunotherapy. - van Maurik, A; Herber, M; Wood, K; Jones, N (2002)
Blockade of CD40-CD154 interactions can facilitate long-term allograft acceptance in selected rodent and in primate models, but, due to the ability of CD154-independent CD8(+) T cells to initiate graft rejection, this strategy is not always effective. In this work we demonstrate that blockade of the CD40-CD154 pathway at the time of transplantation enables the generation of donor alloantigen-specific CD4(+)CD25(+) regulatory T cells, and that if the regulatory cells are present in sufficient numbers they can suppress allograft rejection mediated by CD154-independent CD8(+) T cells.